[OP.1C.04] STRUCTURAL AND FUNCTIONAL ARTERIAL ABNORMALITIES IN FIBROMUSCULAR DYSPLASIA ARE IN THE CONTINUUM OF HYPERTENSION: AN IMAGING AND BIOMECHANICAL STUDY. (September 2016) - Marais, L.; Boutouyrie, P.; Khettab, H.; Boulanger, C.; Lorthiroir, A.; Frank, M.; Niarra, R.; Renard, J.; Chambon, Y.; Jeunemaitre, X.; Zidi, M.; Plouin, P.-F.; et al.
Abstract : Objective: Fibromuscular dysplasia (FMD) is a non-atherosclerotic non-inflammatory arterial disease, which occurs mostly in middle-aged women and affects medium-sized arteries. We previously showed abnormalities within common carotid artery (CCA) wall, with the presence of triple signal (TS) at ultrasound suggesting the presence of supplementary layers. We aimed at coupling TS presence with microconstituents of the vessel wall, derived from fitting of the pressure-diameter curve. Design and method: We included 50 non-smoking patients with multifocal FMD, 50 essential hypertensive (EH) patients and 50 healthy subjects (HS) matched for age, sex, ethnicity and BP (EH and FD). TS score from the right and left CCA ranging from 2 (normal) to 14 (most advanced) were assessed from 15-MHz echotracking system coupled with aplanation tonometry. Microconstituents of the CCA were derived from inverse-problem resolution using non-linear least-squares method. The strain-energy function included 14 parameters representing geometry (opening-angle, reference radius, in vivo axial stretch), perivascular tethering, and wall material coefficients (elastic modulus, fiber orientation). Results: FMD, EH and HS were well matched. TS was significantly and positively associated with age, hypercholesterolemia, aortic stiffness and carotid intima media thickness (IMT). In multivariate analysis, age, hypercholesterolemia and IMT were significantly associated with TS, explaining 9.5% of its variance. TS was more frequent in FMD than HS (49% vs 16%, p < 0.01), and HT (32%, p = 0.08). As expected, when the whole population was considered (n = 150), we observed significant correlations between age, BP and several microconstituents: particularly, residual stress was lower, and longitudinal and circumferential collagen fibers were stiffer with increasing age and BP (all p < 0.01). TS was positively associated with circular collagen mediated-stiffness (p < 0.01), independently of age and BP levels. Conclusions: We confirmed that FMD is associated with higher frequency of TS, but with overlap with matched EH and HS. The strong association between TS and carotid remodeling, independently of age and BP, suggests that it corresponds to the muscular transition of an elastic artery wall in parallel with the hypertrophic process (Sarkola T et al. Atherosclerosis 2010). The association of TS with circular collagen stiffness suggests that TS has subtle but measurable mechanical consequences.